The Impact of Brick Business on the Absorption of Local Labor in Sukodadi Village, Sukarami District, Palembang City from the Perspective of Hifzul Maal - Said Abdullah Syahab; Abdan Sakura; Abubakar Sidik (CV. Era Digital Nusantara, 2026)
Brick-making businesses are labor-intensive micro-enterprises that play an important role in absorbing local labor in Sukodadi Village, Sukarami District, Palembang City. These businesses provide employment opportunities for low-educated communities who have limited access to formal jobs. However, labor practices remain largely informal, with unclear wage standards and limited worker protection, which require evaluation from the Hifzul Mal perspective. This study aims to analyze the impact of brick-making businesses on local labor absorption, identify factors encouraging local residents to work in this sector, and assess labor management practices based on Hifzul Mal principles. The research adopts a qualitative field research approach. Data were collected through interviews, observation, and documentation, and analyzed using data reduction, data display, and conclusion drawing with triangulation. The findings show that brick-making businesses have a positive impact on local labor absorption, particularly in manual production processes. Key factors include limited formal job opportunities, low education levels, and easy access to work. Nevertheless, from the Hifzul Mal perspective, labor management has not fully reflected principles of justice, worker protection, and sustainability, indicating the need for improved business governance.